Allergic and hypersensitivity conditions in non‐specialist care: Flow diagrams to support clinical practice. Issue 9 (19th March 2022) - Ryan, Dermot; Flokstra – de Blok, Bertine M. J.; Clark, Evangéline; Gaudin, Clara; Mamodaly, Myriam; Kocks, Janwillem; van der Velde, Jantina Lucia; Angier, Liz; Romberg, Kerstin; Gawlik, Radek; Demoly, Pascal; Tanno, Luciana Kase
Abstract: Most patients presenting with allergies are first seen by primary care health professionals. The perceived knowledge gaps and educational needs were recently assessed in response to which the LOGOGRAM Task Force was established with the remit of constructing pragmatic flow diagrams for common allergic conditions in line with an earlier EAACI proposal to develop simplified pathways for the diagnosis and management of allergic diseases in primary care. To address the lack of accessible and pragmatic guidance, we designed flow diagrams for five major clinical allergy conditions: asthma, anaphylaxis, food allergy, drug allergy, and urticaria. Existing established allergy guidelines were collected and iteratively distilled to produce five pragmatic and accessible tools to aid diagnosis and management of these common allergic problems. Ultimately, they should now be validated prospectively in primary care settings. Abstract :